2020
DOI: 10.1074/jbc.ra120.013461
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry characterization of light chain fragmentation sites in cardiac AL amyloidosis: insights into the timing of proteolysis

Abstract: Amyloid fibrils are polymeric structures originating from aggregation of misfolded proteins. In vivo, proteolysis may modulate amyloidogenesis and fibril stability. In light chain (AL) amyloidosis, fragmented light chains (LCs) are abundant components of amyloid deposits; however, site and timing of proteolysis are debated. Identification of the N- and C-termini of LC fragments is instrumental to understanding involved processes and enzymes. We investigated the N- and C-terminome of the LC proteoforms in fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 51 publications
9
67
0
Order By: Relevance
“…In our fibrils formed in vitro we only detected a fragment of almost the entire variable domain in P006 (pH 3), in addition to shorter fragments of the same region. We could find many similar C-terminal fragments, which is in accordance with the heterogeneous fragmentation positions reported recently 71 . The fragments we have detected are mostly rather short with an average molecular weight of 3.8 kDa.…”
Section: /19supporting
confidence: 92%
See 1 more Smart Citation
“…In our fibrils formed in vitro we only detected a fragment of almost the entire variable domain in P006 (pH 3), in addition to shorter fragments of the same region. We could find many similar C-terminal fragments, which is in accordance with the heterogeneous fragmentation positions reported recently 71 . The fragments we have detected are mostly rather short with an average molecular weight of 3.8 kDa.…”
Section: /19supporting
confidence: 92%
“…Previous studied already demonstrated that short peptides of 12 residues of the variable and constant domain of an amyloidogenic λ LC can form fibrillar structures in vitro 72 . It has been proposed that at least some proteolytic cleavage events happen after the assembly into amyloid fibrils in vivo 71,73 . This is likely also to be the case for our amyloid fibrils assembled in vitro.…”
Section: /19mentioning
confidence: 99%
“…In particular, the N-and C-terminal residues of fragments were chemically derivatized, and the labeled residues were identified by LC-MS/MS and bioinformatics [87]. The data showed that fragmentations mainly occurs in the C L ; the cleavage sites that generate LC fragments are mostly located in poorly structured regions of the fibrillar structure, suggesting that the ensemble of proteolytic events observed in mature ex vivo fibrils largely reflects extensive proteolytic remodeling of the preformed aggregates [87]. Amyloidogenic LCs, however, are not the only molecular species present in the deposits.…”
Section: The Al Amyloid Proteome: Disease Typing Characterization Of Deposited Lc Proteoforms and The Amyloid Environmentmentioning
confidence: 99%
“…The pathogenetic role of proteolysis in AL (i.e., whether it precedes or follows LC deposition) is still debated, and the discussion of this topic is beyond the scope of this review. Indeed, new findings on the features of amyloid LC fragments come from a recent proteomic study performed by our group, dedicated to the investigation of the termini of these proteoforms [ 87 ] in ex vivo cardiac deposits. In particular, the N- and C-terminal residues of fragments were chemically derivatized, and the labeled residues were identified by LC-MS/MS and bioinformatics [ 87 ].…”
Section: The Al Amyloid Proteome: Disease Typing Characterization Of Deposited Lc Proteoforms and The Amyloid Environmentmentioning
confidence: 99%
“…Full-length LCs are more stable in vitro and less prone to aggregation under native-like conditions than their component VL-domains [9,11]. AL fibrils appear to be primarily composed of fragments of LCs, although the nature of this cleavage is unknown and may happen after deposition as amyloid [10,[12][13][14][15][16]. The nascent amyloid fibrils must be stable enough to recruit new protein molecules and grow into mature fibrils, rather than dissociate.…”
Section: Introductionmentioning
confidence: 99%